2002
DOI: 10.1074/jbc.m106915200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorylation on the Structure and Fold of Transactivation Domain of p53

Abstract: (1). A major response is to halt cell cycle progression with corresponding activation of genes needed for DNA repair. A second kind of response is apoptosis (2). Genotoxic stresses activate many cellular kinases that phosphorylate various serine and threonine residues in p53, as well as enzymes that cause lysine acetylations (3). Presently, at least 12 serine/threonines and 2 lysines are known to be modified in p53 and there may be more modification sites. This signaling system and the code of post-translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 35 publications
7
45
1
1
Order By: Relevance
“…Most of the acetylation events occurred within the C-terminal 100 amino acids and are contributed to by p300/CBP and PCAF Liu et al, 1999;Ito et al, 2001). The functional interaction between acetylation and phosphorylation has been demonstrated previously; phosphorylation at the p53 N terminus potentiated acetylation at the C terminus (Lambert et al, 1998;Sakaguchi et al, 1998), possibly through an enhanced interaction between p53 and the acetylases as a result of phosphorylation (Lambert et al, 1998;Kar et al, 2002). In our study, we have demonstrated that p53 C-terminal phosphorylation by CHK1 and CHK2 may also modulate C-terminal acetylation.…”
Section: Role Of P53 C-terminal Phosphorylation By Chk1 and Chk2 In Pmentioning
confidence: 95%
See 3 more Smart Citations
“…Most of the acetylation events occurred within the C-terminal 100 amino acids and are contributed to by p300/CBP and PCAF Liu et al, 1999;Ito et al, 2001). The functional interaction between acetylation and phosphorylation has been demonstrated previously; phosphorylation at the p53 N terminus potentiated acetylation at the C terminus (Lambert et al, 1998;Sakaguchi et al, 1998), possibly through an enhanced interaction between p53 and the acetylases as a result of phosphorylation (Lambert et al, 1998;Kar et al, 2002). In our study, we have demonstrated that p53 C-terminal phosphorylation by CHK1 and CHK2 may also modulate C-terminal acetylation.…”
Section: Role Of P53 C-terminal Phosphorylation By Chk1 and Chk2 In Pmentioning
confidence: 95%
“…Because N-terminal phosphorylation at Ser15 and Ser20 has been shown to augment p53 acetylation, possibly through an increased interaction with p300/CBP (Lambert et al, 1998;Sakaguchi et al, 1998;Kar et al, 2002), we therefore examined these mutants for their N-terminal phosphorylation status. Consistently, the 377/378A mutant displayed significantly higher Ser20 phosphorylation ( Figure 6B, lane 5) and showed a better interaction with p300 ( Figure 6C, lane 3) compared with the other mutants.…”
Section: C-terminal Phosphorylation Of P53 Differentiallymentioning
confidence: 99%
See 2 more Smart Citations
“…Its transactivation domain, located at the N-terminus of the protein, is responsible for binding proteins such as MDM2, which down-regulates the levels of p53 [16]; hence, the transactivation domain of p53 is emerging as one of the most important regions in p53 function. Nuclear magnetic resonance (NMR) [17,18], combined NMR and small-angle X-ray scattering [19], paramagnetic relaxation enhancement [20] and computer simulations [21] have shed some light on the structural features of the transactivation domain of p53. More recently, Lowry et al proposed an ensemble of three-dimensional structures of the 71-residue transactivation domain of p53 based on distance constraints derived from paramagnetic relaxation enhancement experiments [20].…”
Section: Introductionmentioning
confidence: 99%